Contribution Of School Principals In Achieving Accredited Schools - Muh. Hizbul Muflihin; Aziz Fuadi (Eduvest - Journal of Universal Studies, 2024)
At present the problem of school graduates is still a central issue in the study of education management in Indonesia. For school levels, the legal basis for accreditation is primarily: Law No. 20 of 2003 Article 60, Government Regulation No. 19 of 2005 Articles 86 & 87 and Minister of National Education Decree No. 87 / U / 2002. Accreditation in the process takes the form of systematic and comprehensive school assessment activities through self-evaluation activities and external evaluations (visitations) to determine an eligibility and school performance is only an instrument. This means that the school will still be of high quality or not very much dependent on the wishes of all school people to work together to realize a quality graduate or not. We need to realize that the realization of accredited schools is also influenced by the persistence and enthusiasm of school principals in encouraging all citizens to make it happen. To improve the quality of schools or madrasah it is necessary to create a school culture, among the benefits of cultural values are; 1) Adaptive culture, 2) Family culture, 3) Culture of achievement, and 4) Bureaucratic culture. Among the duties of the existing principal. So the task as a manager in supervising education is very basic, because it relates to the quality of education. Among the duties of the principal are; arrange planning, organize activities, direct activities, coordinate activities, carry out supervision, evaluate activities, hold meetings, make decisions, organize the learning process, organize schools with the community.